2015
DOI: 10.1080/15299732.2015.1018475
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Effects of Stressful Childhood Experiences on Delusions and Hallucinations

Abstract: The association between stressful childhood experiences (SCE) and psychotic symptoms is still not clearly understood, and different causal pathways have been proposed. Generalized estimating equation modeling was used to test the dose-response relationship between SCE and delusions and hallucinations at baseline and follow-up periods and the possible confounding effects of dissociation on this relationship. The prevalence of SCE in individuals with psychotic disorders was high, with more co-occurring SCE categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 55 publications
3
37
0
Order By: Relevance
“…National comorbidity studies and meta-analysis have reported a potentially causal relationship between cumulative TLEs exposure and psychosis (26, 53, 54). Our data are consistent with other studies that show that the overall lifetime TLE exposure is significantly higher in the African-American population (47, 55, 56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…National comorbidity studies and meta-analysis have reported a potentially causal relationship between cumulative TLEs exposure and psychosis (26, 53, 54). Our data are consistent with other studies that show that the overall lifetime TLE exposure is significantly higher in the African-American population (47, 55, 56).…”
Section: Discussionmentioning
confidence: 99%
“…Childhood adversity, as well as broader lifetime trauma, tends to be correlated with additional environmental factors, including prenatal insults [such as alcohol exposure during gestation (24), poverty/structural adversity 1 , and personal substance use (25)]. Muenzenmaier et al (26), have described “complex trauma reactions” triggered by cumulative social adversities and TLEs leading to a broad range of presenting psychotic or psychotic-like symptoms, including dissociation, flashbacks, hallucinations, and paranoid ideation. Recent debates have centered on the differences and overlap between dissociative phenomena, including hallucinations, and psychotic symptoms as they manifest across traditional diagnostic boundaries [e.g., Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to SLEs are associated with increased risk for depressed mood, anxiety, eating disorders, suicidality, substance use, and psychosis symptoms in later adolescence (29, 8185). Current findings on the SLE–psychosis risk relationship are inconclusive; some cited a positive relationship (39, 51, 86, 87) while others did not (43, 47, 48, 57). Kraan and colleagues (5) indicated that recent SLEs were less commonly endorsed by CHR youth than HC, which may be due to increasing negative symptoms of psychosis (e.g., increased avolition, social withdrawal) that limit activities.…”
Section: Sles In the Chr Populationmentioning
confidence: 96%
“…Compared to adult participants with no history of CT, those with exposure to four or more traumas were at substantial risk (4- to 12-fold) for developing substance use, depression, and suicidality (38). Thus, several studies on stress and trauma posit that the experience of CT and prolonged early stressors may contribute to the increased risk of future SMI (2434, 3941). …”
Section: Trauma Experiences In the Chr Populationmentioning
confidence: 99%
“…Thus, we need more complex models that account for both the type and number of CAs are needed to determine whether the associations of CAs with PEs are specific to certain types of experiences but not others, and how increasing levels of exposure influence the risk for PEs. Indeed, several prior studies have documented a dose-response relationship between number of CAs and lifetime prevalence of PEs (Janssen et al , 2004, Shevlin et al , 2007, Wigman et al , 2011a, Wigman et al , 2011b, Bentall et al , 2012, Murphy et al , 2013, Muenzenmaier et al , 2015). …”
Section: Introductionmentioning
confidence: 99%